Efektivitas Penggunaan Media Video dan Media Leaflet Terhadap Perubahan Pengetahuan dan Sikap Siswa Tentang Bahaya Napza di SMP Negeri 3 Mojosongo Boyolali - Purnama, Arif Putra; , Abi Muhlisin, SKM, M.Kep; , Kartinah, A.Kep, S.Kep (2013)
Abuse of drugs among school students already at the stage of concern. Data for the year 2011 in Boyolali district there are 784 people are positive people who use drugs, from the data therein, including students. Lack of knowledge and attitude of students about the dangers of drugs to be one of the causes why teens can go to use drugs. One of efforts to improve students' knowledge and attitude conducted use media Video and leaflet about dangers of drugs. The objective research is to know effectiveness of video and leaflet medias to change of student's knowledge and attitude of dangers drug in Mojosongo junior high school 3 of Boyolali. This kind of research is quasi experimental design, with pretest-postest group design. Sample research are VIII classes with 70 students, then divided two groups, 35 students with video media group and 35 students with media leaflets. Taking Sampling use proportional random sampling. Instrument research use knowledge and attitude questionnaire given before and after counseling. Analysis research data use comparative test, Wilcoxon rank test, paired sample test and independent sample test. Research results that majority of respondents from media video and a lot of counseling before leaflet low and after counseling, knowledge low decrease. Respondent's attitude before counseling a bad lot, after counseling much good. Results test of comparative effectiveness that knowledge and change attitudes respondents video and leaflet media. Media video more effective to increase respondent's knowledge with video than knowledge with leaflet media with gap score is 1.65 point. result statistic test with p = 0.04. Media video more effective in attitude change video's respondent than leaflet respondents with gap score is 1.80 point. Result of statistic test with p = 0.02.